2019
DOI: 10.1161/circulationaha.118.037702
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Women

Abstract: Background: Despite recent progress in profiling of risk for sudden cardiac death (SCD) and prevention and intervention of cardiac diseases, SCD remains a major cause of death. Among women, the incidence of SCD is significant, but lower than in men, particularly in the premenopausal and early postmenopausal years. Possibly, as a consequence of the difference in population burden, the mechanisms and risk markers of SCD are not as well defined for women. The aim of this study was to determine the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 26 publications
5
81
0
4
Order By: Relevance
“…Arrhythmias have been found to increase with aging and are a major risk factor for sudden cardiac death (SCD). While ischemia is the major cause of SCD [49], women are more likely to have a nonischemic cause of SCD and female subjects with SCD are older than men [50].…”
Section: Cardiac Senescencementioning
confidence: 99%
“…Arrhythmias have been found to increase with aging and are a major risk factor for sudden cardiac death (SCD). While ischemia is the major cause of SCD [49], women are more likely to have a nonischemic cause of SCD and female subjects with SCD are older than men [50].…”
Section: Cardiac Senescencementioning
confidence: 99%
“…Further definitions of these conditions have been previously described. 5 The "other" SCD victims included individuals with the following conditions: myocarditis, cardiac anomaly, and normal autopsy individuals (e.g. individuals with a channelopathy).…”
Section: Fingesturementioning
confidence: 99%
“…By contrast, nonischemic pathology, such as primary myocardial fibrosis, valvular heart disease, and arrhythmogenic right ventricular cardiomyopathy, occurs more commonly in women with SCD compared to men with SCD. [5][6][7] SCD is often the first manifestation of heart disease, particularly for women; several studies have found that women are less likely than men to have a prior history of known cardiac disease. 4,8 It has been hypothesized that SCD is a much more heterogeneous condition in women, potentially due to the different underlying diseases, leading to differences in the associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the Fingesture study, women were considerably older at the time of sudden death, and more commonly had non-ischemic causes. Women were also more likely to have a prior normal clinical nding than men, but an increased biological marker for sudden death risk criteria for left ventricular hypertrophy with repolarization abnormalities was more commonly observed in women [13]. In addition to these non-modi able risk factors (sex, hormones, etc.…”
Section: Discussionmentioning
confidence: 99%